Diseño y elaboración de material didáctico en kichwa para el aprendizaje de ciencias sociales en quinto y sexto año de educación general básica en la escuela Tahuantinsuyo de la parroquia Quinchuqui, cantón Otavalo - Ichau Rojas, Mayra Alejandra (2015)
This product grade is designed for school Tahuantinsuyo Otavalo, Imbabura province with students in fifth and sixth year of Basic General Education. The product came from the need to increase educational material in the area of Social Sciences for this institution. The prepared material is a model of the Tahuantinsuyo and a puzzle about the world's problems. The work presents a literature research on teaching resources; on the characteristics physical, psychological, cognitive and social needs of students pursuing these levels; on the subject of social science and its contents. An explanation of the importance of this resource in Kichwa language , so it also makes it discloses the material designed and crafted to be useful for both the teacher and the student to achieve a creative, dynamic learning and especially flashy.